Returns to Scale and Elasticity of Natural Rubber Production in Kerala, India. - Dr. Revathi K Sivadas, Mr. Jovin P John (International Journal of Modern Agriculture, 2021)
In India, the state of Kerala has a positive approach on the cultivation of rubber and it provides gigantic contribution in country’s gross national income. Eventually, the rubber cultivators have been passing through various positive and negative upshots. The study primarily focussed to analyse natural rubber production in Kerala, India and it observed returns to scale, determinants and elasticities of natural rubber production. Both primary and secondary data applied in the present study. The primary data were gathered through structured questionnaires from 384 respondents. For the data collection random sampling technique were applied. The secondary data is carried out a time span of 34 years. The secondary data were analysed through curve estimation and regression model. From the curve estimation model found that three different stages of production namely, increasing returns, constant returns and diminishing returns especially in the time series data. The coefficient magnitude of natural rubber’s production function estimated from primary data and in which applied multiple regression model. The result summary explained the elasticity of natural rubber production is in the stages of diminishing returns. The study found that the most of the determinants have positive significant effect on natural rubber production in Kerala.